Inducible Nitric Oxide Synthase Immunoreactivity in the Alzheimer Disease Hippocampus: Association with Hirano Bodies, Neurofibrillary Tangles, and Senile Plaques - Sunhee C. Lee; Meng‐Liang Zhao; Asao Hirano; Dennis W. Dickson (1999)
Inducible nitric oxide synthase (iNOS) is involved in the generation of nitric oxide, a molecule with multiple biological activities. Although iNOS expression may be part of antimicrobial armamentarium, inappropriate expression of iNOS can potentially lead to damage to the host. In this report, we determined the expression of iNOS by immunocytochemistry in the hippocampus of the Alzheimer brains (AD) as well as in young and old normal brains. The results showed localization of iNOS immunoreactivity to Hirano bodies of the AD hippocampus. In addition, small granular iNOS immunoreactive profiles were detected associated with senile plaques and extracellular neurofibrillary tangles. In the hippocampus of control brains, morphologically similar profiles were immunoreactive for iNOS, but in far fewer numbers than in AD hippocampus. The results suggest that iNOS is expressed in a subset of pyramidal neurons in the AD hippocampus, and that iNOS may be involved in the pathogenesis of neuronal degeneration in AD.